Factores que intervienen en el proceso de gestión de cobranza en el Gobierno Autónomo Descentralizado Municipal del Cantón Babahoyo en el periodo 2022. - Ponce Pérez, Juan Diego (2023)
During the year 2022, the debt collection management at the Autonomous Decentralized Municipal Government (GADM) of Babahoyo Canton was influenced by several key factors. Firstly, the economic situation of the taxpayers played a significant role. The financial stability and ability to pay of citizens were affected by economic fluctuations, directly impacting their willingness and capability to meet their tax obligations. This varying economic scenario conditioned the effectiveness of debt collection management, requiring flexible and adaptive approaches. Additionally, local and national regulations and norms also impacted the GADM's debt collection management process. Changes in tax laws, governmental policies, and legal provisions related to municipal taxes and debts affected the collection strategy. The need to stay updated and in compliance with these regulations posed a constant challenge to the effectiveness of collection practices. Another relevant factor was the infrastructure and technology used in the debt collection management process. The availability and efficiency of information systems, specialized software, and communications played a critical role in the effectiveness of debt collection. Adequate technological infrastructure allowed for more agile, automated, and precise management, facilitating debt recovery and optimizing the overall process. However, limitations in this aspect could have posed an obstacle to optimal and efficient debt collection management.